Coating for preventing surface layer of aluminum bar from being oxidized

By preparing porous composite ceramic inner coating and high-entropy alloy outer coating on the surface of the aluminum rod, the problems of oxidation and insufficient performance of the aluminum rod are solved, and the effect of improving the comprehensive performance of the aluminum rod and expanding the application range is achieved.

CN119876945APending Publication Date: 2025-04-25江苏中机恒亚轻合金有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410536508.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Aluminum rods are prone to oxidation in the air, resulting in an uneven oxide film on the surface, affecting its performance. Moreover, aluminum has low hardness, poor wear resistance and corrosion resistance, which limits its application range.

Method used

The double-coated structure of porous composite ceramic inner coating and high-entropy alloy outer coating was adopted to prepare a composite ceramic inner coating of alumina and boron carbide by microarc oxidation, and the high-entropy alloy outer coating was prepared by laser cladding.

Benefits of technology

This coating structure makes the aluminum rod have the advantages of ceramic materials and high entropy alloys, significantly improving its hardness, thermal stability, oxidation resistance and corrosion resistance, thereby expanding its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004819756360000111
    Figure BDA0004819756360000111
  • Figure BDA0004819756360000121
    Figure BDA0004819756360000121
Patent Text Reader

Abstract

The invention discloses a coating for preventing the surface layer of an aluminum bar from being oxidized. The coating is composed of a porous composite ceramic inner coating and a high-entropy alloy outer coating. The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, the porous composite ceramic inner coating comprises aluminum oxide and boron carbide, the coating is of a porous structure, pores are uniformly distributed, and the pore diameter is small. The preparation method of the high-entropy alloy outer coating is a laser cladding method, the components of the alloy are Al-Ti-Cr-Fe-Ni-Co, and the high-entropy alloy is simple in crystal structure and excellent in comprehensive performance and has an obvious improvement effect on an aluminum matrix as a coating. The coating is tightly combined with an aluminum matrix, the preparation method is simple and controllable, the strength and hardness of the aluminum bar are enhanced, the high-temperature oxidation resistance is good, the oxidation weight increment is remarkably reduced, and the comprehensive performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal coatings, in particular to a composite coating for preventing aluminum rods from being oxidized. Background Art

[0002] Aluminum has the characteristics of low density and high strength, excellent comprehensive mechanical properties, and good molding processability. It has extremely important applications in aerospace, military industry, automobile manufacturing and other fields. However, aluminum itself has active chemical properties. When the matrix is ​​exposed to the air, it is easily oxidized, forming an amorphous oxide film on the surface, resulting in uneven distribution of components and structures, which affects the performance. In addition, aluminum has low hardness, poor wear resistance and corrosion resistance, and these shortcomings also limit its scope of application. Therefore, it is usually necessary to adopt a surface treatment process to prevent the surface oxidation of the aluminum matrix and improve the comprehensive performance to meet its application in more demanding environments. Micro-arc oxidation technology, also known as micro-plasma oxidation technology, has the advantages of environmentally friendly electrolyte, simple process, easy equipment operation, strong processing capacity, and controllable ceramic membrane structure composition. By passing current into the electrolyte, micro-arc discharge is generated on the metal surface as the anode, and then a series of complex reactions such as electrochemistry, thermochemistry, and plasma chemistry occur. Through the interaction of these reactions, an oxide ceramic film is grown in situ on the metal surface. By increasing the voltage appropriately, high temperature and high pressure will be instantly generated on the anode metal surface, breaking down the oxide film and forming a ceramic film with a porous structure. By doping other ceramic particles in the electrolyte as a reinforcement, the composition and morphology of the coating can be changed to form a composite ceramic coating with good comprehensive performance. High entropy alloy is an alloy composed of five or more elements in an equiatomic ratio or an equiatomic ratio, and the atomic proportion of each element is between 5% and 35%. Due to the high entropy effect, most high entropy alloys tend to be simple face-centered cubic or body-centered cubic structures, so they have many excellent properties such as high strength, high hardness, oxidation resistance, and corrosion resistance. As a coating, it can well improve the comprehensive performance of the substrate material. High entropy alloys need a high cooling rate to form a simple crystal structure, so the preparation of high entropy alloy coatings usually adopts laser cladding technology. Laser cladding is to use laser beam irradiation to generate high energy, melt the cladding material pre-placed on the surface of the alloy substrate, and then rapidly cool and solidify to generate a coating combined with the alloy substrate. Laser cladding technology has the advantages of controllable coating thickness, strong bonding with the substrate, and high density. It can give full play to the superiority of various performances of high entropy alloy coatings, which is of great significance to the expansion of the application range of high entropy alloy coatings. Summary of the invention

[0003] Technical problem to be solved: The technical problem to be solved by the present invention is to provide a coating for preventing oxidation of the surface of an aluminum rod.

[0004] Technical solution: A coating for preventing oxidation of the surface of an aluminum rod, wherein the anti-oxidation coating is composed of a double coating of a porous composite ceramic inner coating and a high entropy alloy outer coating. Preferably, the porous composite ceramic inner coating comprises components of aluminum oxide and boron carbide. Preferably, the porous composite ceramic inner coating is prepared by micro-arc oxidation, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide are dissolved in deionized water in proportion, and boron carbide nanoparticles are added, and ultrasonic stirring is performed for 60 to 80 minutes to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote the circulation convection of the electrolyte, the positive and negative voltage difference is set to 380 to 420V, the oxidation time is 20 to 60min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed. Preferably, in the electrolyte described in step S12, the concentration of sodium silicate is 5.0-10.0 g / L, the concentration of sodium hydroxide is 1.0-2.0 g / L, and the concentration of boron carbide nanoparticles is 0.3-0.5 g / L. Preferably, the high entropy alloy outer coating has the following atomic percentage composition: Al: 30-35 parts; Ti: 20-25 parts, Cr: 20-25 parts; Fe: 5-10 parts; Ni: 5-10 parts; Co: 5-10 parts. Preferably, the preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The raw material powder is evenly mixed in a ball mill at a speed of 300 to 400 r / min for 2 to 5 h; S23. A polyethylene solution having a concentration of 2 to 5% is prepared and heated in a water bath to completely dissolve the polyethylene in water; S24. The uniformly mixed alloy powder and polyethylene solution are prepared into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness is 0.7 to 1.1 mm, and placed in an oven for drying at a drying temperature of 80 to 100 ° C and a drying time of 3 to 6 h; S25. Place the powder-coated aluminum rod on the operating platform, introduce argon as a protective gas, and perform laser cladding with a scanning speed of 4 to 8 mm / s, a power of 2 to 5 kW, a spot diameter of 3 to 6 mm, and an argon gas flow rate of 10 to 20 L / min. After cladding, a high-entropy alloy coating is formed on the surface of the aluminum rod. Preferably, the porous ceramic inner coating has a thickness of 20 to 30 μm and a surface roughness of ≤5.0 μm. Preferably, the thickness of the high entropy alloy outer coating is 0.4-0.6 mm, and the particle size range of the raw material powder is 5-20 μm. Beneficial effects: Compared with the prior art, the present invention has the following characteristics: The present invention uses micro-arc oxidation and laser cladding to prepare porous composite ceramic inner coating and high entropy alloy outer coating on the surface of aluminum rod, respectively, to modify the surface of aluminum rod. The surface of aluminum rod is coated with high-hardness and high-stability ceramic particles and oxidation-resistant and corrosion-resistant high entropy alloy. The composite coating can make aluminum have the characteristics of both ceramic material and high entropy alloy, obtain good comprehensive performance, and expand the scope of application. Ceramic materials have high hardness, high thermal stability, and good wear resistance, corrosion resistance, and electrical insulation. As a reinforcement of aluminum, they can effectively improve the comprehensive performance of the aluminum matrix and expand its application range. The porous ceramic coating is prepared on the surface of the aluminum rod by micro-arc oxidation. The aluminum rod is used as the anode material and reacts with the electrolyte to generate aluminum oxide in situ. At the same time, the boron carbide particles added to the electrolyte will also be deposited at the anode to form a composite coating with aluminum oxide. When the voltage is high, electron breakdown will occur and the coating will form a porous structure. Simple oxide ceramic coatings are prone to failure during friction. Adding high-hardness boron carbide particles can effectively improve the wear resistance and thermal stability of the coating, and obtain a composite ceramic coating with excellent mechanical properties. The porous structure has good adsorption and filtration functions, which can effectively improve the oxidation resistance and corrosion resistance of the alloy matrix. At the same time, the holes can provide attachment sites for the alloy particles of the outer coating, so that the inner and outer coatings can be better combined. High entropy alloys have four major effects: high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect. They usually have high strength and hardness, as well as good oxidation resistance and corrosion resistance. High entropy alloys tend to have simple face-centered cubic or body-centered cubic structures, which can effectively avoid the appearance of embrittlement phases during laser cladding and affect the structure and performance of the coating. In addition, high entropy alloy coatings are prepared on the surface of the substrate by laser cladding. Under the high energy of the laser beam, the alloy reacts with the boron carbide of the inner coating to generate AlB2, TiC, TiB2 and other ceramic reinforcement phases in situ. These ceramic phases play a role in fine grain strengthening in the alloy. While improving the hardness and stability of the coating, it also suppresses the problem of poor wettability between the ceramic coating and the alloy coating, making the coatings more tightly bonded and making the cladding layer more uniform and dense. Compared with the prior art, the present invention has the following advantages and positive effects: 1. The present invention combines the high hardness and high thermal stability of the ceramic coating with the anti-oxidation and corrosion resistance of the high entropy alloy coating, so that the aluminum rod has excellent comprehensive performance. 2. The present invention utilizes a micro-arc oxidation method to prepare a porous composite ceramic inner coating. The micro-arc oxidation method has a stable process, high processing efficiency, and the electrolyte does not pollute the environment. It can efficiently prepare a coating with a complete structure and stable performance. 3. The present invention utilizes a laser cladding method to prepare a high entropy alloy outer coating. The laser cladding method has a high degree of automation, controllable cladding layer thickness, high cladding layer quality, and can effectively improve the surface performance of the aluminum rod. DETAILED DESCRIPTION In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. Specific preferred examples are as follows: Embodiment 1: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 60 min to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation convection of the electrolyte, the positive and negative voltage difference is set to 380V, the oxidation time is 60min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; Preferably, in the electrolyte of step S12, the concentration of sodium silicate is 5.0 g / L, the concentration of sodium hydroxide is 1.0 g / L, and the concentration of boron carbide nanoparticles is 0.3 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 35 parts; Ti: 20 parts, Cr: 25 parts; Fe: 5 parts; Ni: 10 parts; Co: 5 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The prepared raw material powder was placed in a ball mill for uniform mixing at a speed of 300 r / min for a ball milling time of 5 h; S23. Prepare a 2% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.7 mm, and placed in an oven for drying at a drying temperature of 100 ° C for a drying time of 3 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 4 mm / s, a power of 2 kW, a spot diameter of 3 mm, and an argon gas flow rate of 10 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 30 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.4 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Embodiment 2: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 80 min to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation and convection of the electrolyte, the positive and negative voltage difference is set to 420V, the oxidation time is 20min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; Preferably, in the electrolyte of step S12, the concentration of sodium silicate is 10.0 g / L, the concentration of sodium hydroxide is 2.0 g / L, and the concentration of boron carbide nanoparticles is 0.5 g / L; Preferably, the high entropy alloy outer coating has the following atomic percentage composition: Al: 30 parts; Ti: 25 parts, Cr: 20 parts; Fe: 10 parts; Ni: 5 parts; Co: 10 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The prepared raw material powder was placed in a ball mill for uniform mixing at a speed of 400 r / min for 2 h; S23. Prepare a 5% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 1.1 mm, and placed in an oven for drying at a drying temperature of 80 ° C and a drying time of 6 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 8 mm / s, a power of 5 kW, a spot diameter of 6 mm, and an argon gas flow rate of 20 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 20 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.6 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Embodiment 3: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 70 min to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation and convection of the electrolyte, the positive and negative voltage difference is set to 390V, the oxidation time is 40min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; In the electrolyte described in step S12, the concentration of sodium silicate is 8.0 g / L, the concentration of sodium hydroxide is 1.6 g / L, and the concentration of boron carbide nanoparticles is 0.4 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 32 parts; Ti: 22 parts, Cr: 23 parts; Fe: 8 parts; Ni: 8 parts; Co: 7 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing, the speed is 340r / min, and the ball milling time is 4h; S23. Prepare a 3% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.8 mm, and placed in an oven for drying at a drying temperature of 95 ° C and a drying time of 3 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 5 mm / s, a power of 3 kW, a spot diameter of 4 mm, and an argon gas flow rate of 18 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 25 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.45 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Embodiment 4: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 65 minutes to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation convection of the electrolyte, the positive and negative voltage difference is set to 400V, the oxidation time is 50min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; In the electrolyte described in step S12, the concentration of sodium silicate is 9.0 g / L, the concentration of sodium hydroxide is 1.8 g / L, and the concentration of boron carbide nanoparticles is 0.45 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 35 parts; Ti: 24 parts, Cr: 21 parts; Fe: 9 parts; Ni: 7 parts; Co: 4 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing, the speed is 380r / min, and the ball milling time is 3h; S23. Prepare a 4% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 1.0 mm, and placed in an oven for drying at a drying temperature of 90 ° C for a drying time of 5 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 7 mm / s, a power of 4 kW, a spot diameter of 5 mm, and an argon gas flow rate of 15 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The porous ceramic inner coating has a thickness of 28 μm and a surface roughness of ≤5.0 μm; The thickness of the high entropy alloy outer coating is 0.5 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Embodiment 5: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 75 minutes to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation convection of the electrolyte, the positive and negative voltage difference is set to 410V, the oxidation time is 30min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; In the electrolyte described in step S12, the concentration of sodium silicate is 6.0 g / L, the concentration of sodium hydroxide is 1.2 g / L, and the concentration of boron carbide nanoparticles is 0.35 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 34 parts; Ti: 25 parts, Cr: 23 parts; Fe: 6 parts; Ni: 5 parts; Co: 7 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing, the speed is 320r / min, and the ball milling time is 5h; S23. Prepare a 2% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.9 mm, and placed in an oven for drying at a drying temperature of 85 ° C and a drying time of 4 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 6 mm / s, a power of 4 kW, a spot diameter of 5 mm, and an argon gas flow rate of 13 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 23 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.55 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Comparative Example 1: A coating for preventing oxidation of the surface of an aluminum rod, wherein the anti-oxidation coating is composed of a double coating of a porous ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating is composed of aluminum oxide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide are dissolved in deionized water in proportion, and ultrasonic stirring is performed for 70 minutes to obtain a composite electrolyte; S13. An aluminum rod is placed in an electrolytic cell as an anode for oxidation, and a mechanical stirring device is used to promote the circulation convection of the electrolyte. The positive and negative voltage difference is set to 400V, and the oxidation time is 40 minutes. After oxidation, an aluminum oxide ceramic coating is formed on the surface of the aluminum rod; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; The electrolyte described in step S12 has a sodium silicate concentration of 7.0 g / L and a sodium hydroxide concentration of 1.4 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 31 parts; Ti: 22 parts, Cr: 23 parts; Fe: 9 parts; Ni: 9 parts; Co: 6 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing, the speed is 360r / min, and the ball milling time is 3h; S23. Prepare a 3% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.7 mm, and placed in an oven for drying at a drying temperature of 90 ° C and a drying time of 3 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 4 mm / s, a power of 2 kW, a spot diameter of 4 mm, and an argon gas flow rate of 16 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 26 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.4 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Comparative Example 2: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a double coating of a dense composite ceramic inner coating and a high entropy alloy outer coating; The dense composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the dense composite ceramic inner coating is a micro-arc oxidation method, which comprises the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 65 minutes to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation convection of the electrolyte, the positive and negative voltage difference is set to 300V, the oxidation time is 50min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; In the electrolyte described in step S12, the concentration of sodium silicate is 5.0 g / L, the concentration of sodium hydroxide is 1.0 g / L, and the concentration of boron carbide nanoparticles is 0.4 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 35 parts; Ti: 21 parts, Cr: 24 parts; Fe: 6 parts; Ni: 7 parts; Co: 7 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing, the speed is 320r / min, and the ball milling time is 4h; S23. Prepare a 2% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.8 mm, and placed in an oven for drying at a drying temperature of 95 ° C and a drying time of 4 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 5 mm / s, a power of 4 kW, a spot diameter of 6 mm, and an argon gas flow rate of 12 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the dense ceramic inner coating is 29 μm; The thickness of the high entropy alloy outer coating is 0.45 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Comparative Example 3: A coating for preventing oxidation of the surface of an aluminum rod, the anti-oxidation coating comprising a porous composite ceramic inner coating and a ternary alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 80 min to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation convection of the electrolyte, the positive and negative voltage difference is set to 400V, the oxidation time is 30min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; Preferably, in the electrolyte described in step S12, the concentration of sodium silicate is 9.0 g / L, the concentration of sodium hydroxide is 1.8 g / L, and the concentration of boron carbide nanoparticles is 0.5 g / L; The ternary alloy outer coating has the following atomic percentage components: Al: 35 parts; Ti: 35 parts, Cr: 30 parts; The preparation method of the ternary alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The configured raw material powder is placed in a ball mill for uniform mixing at a speed of 380 r / min and a ball milling time of 2 h; S23. Prepare a 4% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 1.0 mm, and placed in an oven for drying at a drying temperature of 85 ° C and a drying time of 6 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 7 mm / s, a power of 5 kW, a spot diameter of 3 mm, and an argon gas flow rate of 20 L / min. After cladding, a ternary alloy coating is formed on the surface of the aluminum rod; The porous ceramic inner coating has a thickness of 22 μm and a surface roughness of ≤5.0 μm; The thickness of the ternary alloy outer coating is 0.55 mm, and the particle size of the raw material powder ranges from 5 to 20 μm. Comparative Example 4: A coating for preventing oxidation of the surface of an aluminum rod, wherein the anti-oxidation coating is composed of a double coating of a porous composite ceramic inner coating and a high entropy alloy outer coating; The porous composite ceramic inner coating comprises aluminum oxide and boron carbide; The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide were dissolved in deionized water in proportion, and boron carbide nanoparticles were added, and ultrasonic stirring was performed for 60 min to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote circulation and convection of the electrolyte, the positive and negative voltage difference is set to 390V, the oxidation time is 60min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed; In the electrolyte described in step S12, the concentration of sodium silicate is 8.0 g / L, the concentration of sodium hydroxide is 1.6 g / L, and the concentration of boron carbide nanoparticles is 0.45 g / L; The high entropy alloy outer coating has the following atomic percentage composition: Al: 35 parts; Ti: 22 parts, Cr: 22 parts; Fe: 10 parts; Ni: 6 parts; Co: 5 parts; The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The prepared raw material powder was placed in a ball mill for uniform mixing at a speed of 400 r / min for 3 h; S23. Prepare a 5% polyethylene solution and heat it in a water bath to completely dissolve the polyethylene in water; S24. The alloy powder and polyethylene solution were mixed into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness was 0.9 mm, and placed in an oven for drying at a drying temperature of 90 ° C and a drying time of 4 h; S25. The powder-coated aluminum rod is placed on the operating platform, argon is introduced as a protective gas, and laser cladding is performed at a scanning speed of 8 mm / s, a power of 4 kW, a spot diameter of 5 mm, and an argon gas flow rate of 14 L / min. After cladding, a high entropy alloy coating is formed on the surface of the aluminum rod; The thickness of the porous ceramic inner coating is 27 μm, and the surface roughness is ≤ 5.0 μm; The thickness of the high entropy alloy outer coating is 0.5 mm, and the particle size of the raw material powder ranges from 20 to 30 μm. The examples and comparative examples were subjected to a constant temperature oxidation test at 800°C to test their oxidation weight gain after 100 hours to characterize the difference in their antioxidant properties. The tensile strength and hardness of the examples and comparative examples were tested using a universal testing machine and a microhardness tester, respectively. Table 1 Performance parameters of various embodiments and comparative examples In summary, compared with the control example, the strength, hardness and oxidation resistance of the aluminum rod anti-oxidation coating prepared by the present invention are significantly enhanced, wherein the oxidation weight gain at 800°C is reduced by more than 50%, and the oxidation resistance is significantly improved. The coating enables the aluminum rod to have excellent comprehensive performance.

Claims

1. A coating for preventing oxidation of the surface of an aluminum rod, characterized in that: The anti-oxidation coating consists of a double coating of a porous composite ceramic inner coating and a high entropy alloy outer coating.

2. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The porous composite ceramic inner coating comprises aluminum oxide and boron carbide.

3. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The preparation method of the porous composite ceramic inner coating is a micro-arc oxidation method, comprising the following steps: S11. Polish the surface of the aluminum rod with sandpaper to remove the surface oxide layer, put it into anhydrous ethanol for ultrasonic cleaning, and rinse it with deionized water; S12. Sodium silicate and potassium hydroxide are dissolved in deionized water in proportion, and boron carbide nanoparticles are added, and ultrasonic stirring is performed for 60 to 80 minutes to obtain a composite electrolyte; S13. The aluminum rod is placed in an electrolytic cell as an anode for oxidation, a mechanical stirring device is used to promote the circulation convection of the electrolyte, the positive and negative voltage difference is set to 380 to 420V, the oxidation time is 20 to 60min, and an aluminum oxide and boron carbide composite ceramic coating is formed on the surface of the aluminum rod after oxidation; S14. Rinse the oxidized aluminum rod with deionized water and dry it to ensure that all impurities are removed.

4. The coating for preventing oxidation of the surface of an aluminum rod according to claim 3, characterized in that: In the electrolyte described in step S12, the concentration of sodium silicate is 5.0-10.0 g / L, the concentration of sodium hydroxide is 1.0-2.0 g / L, and the concentration of boron carbide nanoparticles is 0.3-0.5 g / L.

5. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The high entropy alloy outer coating has the following atomic percentage composition: Al: 30-35 parts; Ti: 20-25 parts, Cr: 20-25 parts; Fe: 5-10 parts; Ni: 5-10 parts; Co: 5-10 parts.

6. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The preparation method of the high entropy alloy outer coating is a laser cladding method, comprising the following steps: S21. Calculate the mass of each raw material powder according to the atomic percentage of the alloy and weigh and configure; S22. The prepared raw material powder is placed in a ball mill for uniform mixing at a speed of 300 to 400 r / min for a ball milling time of 2 to 5 h; S23. A polyethylene solution having a concentration of 2 to 5% is prepared and heated in a water bath to completely dissolve the polyethylene in water; S24. The uniformly mixed alloy powder and polyethylene solution are prepared into a paste, coated on the surface of the aluminum rod with a ceramic coating, the coating thickness is 0.7 to 1.1 mm, and placed in an oven for drying at a drying temperature of 80 to 100 ° C and a drying time of 3 to 6 h; S25. Place the powder-coated aluminum rod on the operating platform, introduce argon as a protective gas, and perform laser cladding with a scanning speed of 4 to 8 mm / s, a power of 2 to 5 kW, a spot diameter of 3 to 6 mm, and an argon gas flow rate of 10 to 20 L / min. After cladding, a high-entropy alloy coating is formed on the surface of the aluminum rod.

7. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The porous ceramic inner coating has a thickness of 20 to 30 μm and a surface roughness of ≤5.0 μm.

8. The coating for preventing oxidation of the surface of an aluminum rod according to claim 1, characterized in that: The thickness of the high entropy alloy outer coating is 0.4-0.6 mm, and the particle size range of the raw material powder is 5-20 μm.

Citation Information

Cited By

  • Laser cladding high-entropy alloy coating and preparation method thereof

    CN122382561A